The Arsenic Methylation Cycle: How Microbial Communities Adapted Methylarsenicals for Use as Weapons in the Continuing War for Dominance - Chen, Jian; Rosen, Barry P. (Frontiers in Environmental Science, 2020)
Arsenic is the most ubiquitous environmental toxin. Most microorganisms have evolved mechanisms to use methylarsenicals as weapons in microbial warfare. This has created cycles of arsenic methylation and demethylation, which constitutes an important part of arsenic biogeochemical cycles and environmental health. Arsenic methylation forms methylarsenite (MAs(III)), arsenobetaine, arsenosugars and the new identified methylarsenical antibiotic, arsinothricin (AST). Bacteria use MAs(III) and AST to gain a competitive advantage over other bacteria. Microbes generate toxic MAs(III) by 1) methylation of arsenite (As(III)) or 2) reduction of methylarsenate (MAs(V)). In air MAs(III) is oxidized to MAs(V), making methylation an detoxification process in aerobes. MAs(V) is continually re-reduced to MAs(III) by other bacteria, giving them a competitive advantage over sensitive bacteria. Because generation of a sustained pool of MAs(III) requires microbial communities, these complex interactions are an emergent property, that is, overall scheme of arsenic-containing antibiotics emerges from interaction of multiple species. In response to production of the antibiotic MAs(III), other members of microbial communities have evolved at least four mechanisms for resistance to MAs(III): 1) ArsH detoxifies MAs(III) by oxidation to nontoxic MAs(V); 2) ArsI degrades MAs(III) by cleavage of the C-As bond to form less toxic As(III); 3) the ArsP efflux permease confers selective resistance to MAs(III); and 4) the unrelated ArsK efflux permease confers resistance to both trivalent inorganic and organoarsenicals. Environmental application of anthropogenic aromatic arsenicals further fuels bacterial warfare and selection for novel resistance mechanisms. In another microbial adaptation to use environmental arsenic as a weapon, some soil bacteria synthesize a methylarsenate analog of the amino acid glutamic acid termed arsinothricin (AST); AST shows a broad-spectrum antibiotic action against both Gram-negative and Gram-positive bacteria. In response to the environmental challenge presented by AST, arsN genes evolved to detoxify it by acetylation of the α-amino group. Thus life has adapted to use environmental arsenic as a weapon in the continuing battle for dominance. Both MAs(III) and AST are natural products with antibiotic-like properties, both are toxic methylarsenicals produced by one microbe to kill off competitors, and resistances have arisen for both.